2016
DOI: 10.1111/pde.13013
|View full text |Cite
|
Sign up to set email alerts
|

How Often are Pediatric Patients with Clinically Amyopathic Dermatomyositis Truly Amyopathic?

Abstract: These data suggest that truly amyopathic JDM is rare and that a thorough workup that includes all five muscle enzymes and MRI may uncover occult myositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
4
13
1
Order By: Relevance
“…In addition, we found that CAJDM patients have less frequent myalgias, arthralgias and fatigue than JDM patients, and none of our patients developed arthritis, in contrast to other reports [3]. We found a similar distribution in the cutaneous manifestations of CAJDM and JDM patients, as reported by others [1,6]. Importantly, calcinosis, vasculitis and lipodystrophy were absent in CAJDM patients, also as previously reported [1,6], although calcinosis was uncommonly seen in one series of CAJDM patients [3].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, we found that CAJDM patients have less frequent myalgias, arthralgias and fatigue than JDM patients, and none of our patients developed arthritis, in contrast to other reports [3]. We found a similar distribution in the cutaneous manifestations of CAJDM and JDM patients, as reported by others [1,6]. Importantly, calcinosis, vasculitis and lipodystrophy were absent in CAJDM patients, also as previously reported [1,6], although calcinosis was uncommonly seen in one series of CAJDM patients [3].…”
Section: Discussionsupporting
confidence: 86%
“…In adults, CADM represents 1020% of the DM population [1,5]. In children, CAJDM constituted 22% of patients with JDM in one clinic population [6], although relatively few cases of CAJDM in other reports suggests that the frequency may be lower in children [3,4]. Melanoma differentiation-associated gene 5 (MDA5) autoantibodies are associated with amyopathic DM and rapidly progressing lung disease in Asian juvenile and Caucasian adult DM patients [710].…”
Section: Introductionmentioning
confidence: 99%
“…True amyopathic JDM however is very rare and mild muscle involvement may be present but missed (13). Amyopathic JDM generally has a relatively mild disease course with fewer systemic manifestations, less required immunosuppressive treatment and a good prognosis (12, 14, 15).…”
Section: Signs Of Systemic Disease Activity In Jdm Based On Affected mentioning
confidence: 99%
“…Some have questioned the concept of CADM with the argument that if an aggressive search for muscle inflammation is carried out [i.e., all five muscle enzymes (aspartate aminotransferase, alanine aminotransferase, lactate dehydrogenase, creatine kinase and aldolase)], as well as magnetic resonance imaging and muscle biopsy), virtually all juvenile-onset CADM patients will be found to have "subclinical" evidence of myositis (9). (Such patients would meet the criteria for the hypomyopathic subtype of CADM).…”
Section: Clinically-amyopathic Dmmentioning
confidence: 99%